2017
DOI: 10.1002/ejhf.750
|View full text |Cite|
|
Sign up to set email alerts
|

Mediterranean diet and risk of heart failure: results from the PREDIMED randomized controlled trial

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 32 publications
3
56
1
4
Order By: Relevance
“…The corrected Table and Figure (see below; all corrections are marked in bold characters) show the corrected estimates for the outcome, as compared with those reported in the original paper. In consistency with the published paper, the unadjusted hazard ratios (HR) did not indicate significant associations for the MedDiet + EVOO [HR 0.63; 95% confidence interval (CI) 0.38–1.04] and MedDiet + nuts (HR 0.91; 95% CI 0.55–1.50), compared with the control group. Results from the multivariate analyses ( Table ) also remained unchanged.…”
Section: Incidence Of Heart Failure During the Trial Period With Actisupporting
confidence: 80%
See 1 more Smart Citation
“…The corrected Table and Figure (see below; all corrections are marked in bold characters) show the corrected estimates for the outcome, as compared with those reported in the original paper. In consistency with the published paper, the unadjusted hazard ratios (HR) did not indicate significant associations for the MedDiet + EVOO [HR 0.63; 95% confidence interval (CI) 0.38–1.04] and MedDiet + nuts (HR 0.91; 95% CI 0.55–1.50), compared with the control group. Results from the multivariate analyses ( Table ) also remained unchanged.…”
Section: Incidence Of Heart Failure During the Trial Period With Actisupporting
confidence: 80%
“…Some departures from the individual randomization protocol affecting a small subset of participants in the PREvención con DIeta MEDiterránea (PREDIMED) trial (at most 14%) have recently been reported in the re‐publication of the main PREDIMED paper . For this reason, the authors wish to make the following clarifications and corrections to their original PREDIMED sub‐study examining the effect of the Mediterranean diets (MedDiets), supplemented with extra‐virgin olive oil (EVOO) or nuts, on the risk of heart failure …”
Section: Incidence Of Heart Failure During the Trial Period With Actimentioning
confidence: 99%
“…Feeding mice with a high‐fibre diet increased the abundance of acetate‐producing gut bacteria, which significantly decreased myocardial hypertrophy and fibrosis (Marques, et al , ). Furthermore, a Mediterranean diet resulted in low TMAO levels, which can consequently prevent cardiovascular consequences and HF (Papadaki, et al , ; Estruch, et al , ). One study specifically demonstrated that ginger supplementation modulated the gut microbiota community, inducing a significant increase in fatty acid metabolism (Wang, et al , ).…”
Section: Gut Microbiota Interventions For Cvdmentioning
confidence: 99%
“…The PREvención con DIeta MEDiterránea (PREDIMED) randomized controlled trial showed the beneficial effects of a Mediterranean diet supplemented with olive oil or nuts on major cardiovascular events . An analysis of HF events in this trial did not show a reduction in HF events . Such analysis was, however, likely underpowered because of the low incidence of these events.…”
Section: Clinical Trialsmentioning
confidence: 97%